Gastos com medicamentos distribuídos em Atenção Primária de Saúde em Fortaleza- Ce e co-fatores influentes do ano de 2007 - Chaves, Elton da Silva (2009)
The increased investment in the acquisition of drugs have shown significant improvements in health indicators and in the Pharmaceutical Assistance (P.A.). Addressing the needs of the population and ensure access to medicines with equity and efficiency has been a major challenge for health authorities. This work started from the need for a diagnosis of resource allocation for P.A. in the administrative areas of Fortaleza and its Health Units (H.U). This is a retrospective analysis of the database with features of ecological and descriptive study where we examined the secondary data acquisition and distribution of drugs between January - December 2007, the H.U. operating in the municipality. The main goal was to determine the distribution of drug costs in Primary Health Care (PHC) in Fortaleza, Brazil between the H.U. and its regional and analyze the associated factors. To this end, characterized the cost of medication by number of patients in each H.U., it was classified according to ATC and scaled up consumption in DDD have been correlated with the characteristics of the service by examining the Pearson correlation test and t - student to identify co-influencing factors. Total expenditure on essential drugs was estimated at R$9.29 million and the per capita expenditure of R$3.82 and spending per patient from R$2,41. The period of the year that more was spent on drugs was in the 2nd quarter (28,36%) and 9,57% in April and 10,46% in June. The region had the highest spending was the Region II (R$ 2.216.886,94) that has a high Human Development Index (HDI). The average cost per patient was highest in Region V (R$2.82) which is concentrated the population with lower income and low HDI. The therapeutic classes with the highest representation were systemic antibiotics (18,8% of total spending, represented mainly by beta-lactam antibiotics, penicillins), followed by antidiabetics (9.4% oral hypoglycemic agents) and with antihypertensive action on the renin-angiotensin (8,6% and 8,2% only with captopril). The most frequently consumed drugs were: captopril (17,2 DDDs / 1,000 patients seen per day), hydrochlorothiazide (11,9) and aspirin (7,9). The Antiasthmatic represented the most expensive (unit price R$20,66 for Beclometasone 250mcg, R$18,36 Beclomethasone 50mcg and Salbutamol 100mg R$8.57) though the relationship cost / DDD were the most costly: Fenoterol 0.5% (R$11,88), penicillin 600.000 UI (R$6.59) and norethisterone 0.35 mg (R$5,03). The quality of P.A. showed no statistically significant association with the cost of medication, but had an inverse correlation (r = -0,110) with a tendency to reduce spending, the presence of the Pharmacist in the H.U. showed a significant positive correlation with the quality of P.A. (p -value = 0,014) and has an economic impact in spending on drugs with potential savings of R$ 0,32 on average per patient. We conclude that despite the efforts of decentralization still there is inequity in the tip of the Public Health System, which in the upper middle class there was a higher resource allocation relating to medicinal products and in the poorest regions of the city with the highest volume of patients served. Per capita spending on essential drugs in PHC Fortaleza and spending per patient are not consistent with the values agreed upon by management levels (R$6.20). It is recommended that the presence of the Pharmacist in the H.U. aimed at rationalizing spending and consumption of drugs contributing to P.A. quality and efficient in Fortaleza.